Association between clinical variables related to asthma in schoolchildren born with very low birth weight with and without bronchopulmonary dysplasia - Emília da Silva Gonçalves; Francisco Mezzacappa-Filho; Silvana Dalge Severino; Maria Ângela Gonçalves de Oliveira Ribeiro; Fernando Augusto de Lima Marson; Andre Moreno Morcilo; Adyléia Aparecida Dalbo Contrera Toro; José Dirceu Ribeiro
Abstract Objective: To assess the prevalence, spirometry findings and risk factors for asthma in schoolchildren who were very low birth weight infants with and without bronchopulmonary dysplasia. Methods: Observational and cross-sectional study. The parents and/or tutors answered the International Study of Asthma and Allergies in Childhood questionnaire. The schoolchildren were submitted to the skin prick test and spirometry assessment. Results: 54 schoolchildren who were very low birth weight infants were assessed and 43 met the criteria for spirometry. Age at the assessment (bronchopulmonary dysplasia=9.5±0.85; without bronchopulmonary dysplasia=10.1±0.86 years) and birth weight (bronchopulmonary dysplasia=916.7±251.2; without bronchopulmonary dysplasia=1171.3±190.5g) were lower in the group with bronchopulmonary dysplasia (p<0.05). The prevalence of asthma among very low birth weight infants was 17/54 (31.5%), being 6/18 (33.3%) in the group with bronchopulmonary dysplasia. There was an association between wool blanket use in the first year of life (p=0.026) with the presence of asthma at school age. The skin prick test was positive in 13/17 (76.5%) and 23/37 (62.2%) of patients with and without asthma, respectively. The schoolchildren with asthma had lower z-score values of forced expiratory flow between 25% and 75% of forced vital capacity (n=16;−1.04±1.19) when compared to the group of patients without asthma (n=27;−0.380.93) (p=0.049). There was no difference between the spirometry variables in the groups regarding the presence or absence of bronchopulmonary dysplasia. Conclusions: Very low birth weight infants with and without bronchopulmonary dysplasia showed a high prevalence of asthma (33.3% and 30.6%, respectively). Pulmonary flow in the small airways was lower in children with asthma.